Space of Geography Content in Social Studies of School Education Curriculum in Nepal - Poudel, Krishna Prasad (The Third Pole: Journal of Geography Education, 2018)
Social studies education (SSE) is placed among the major academic disciplinary subjects within the school curriculum even from the primary/basic to the secondary level. It is a compulsory subject in the Secondary Education Examination (SEE) as well as it was also in the School Leaving Certificate (SLC) Examination. Importance of the subject itself has no question, despite that the content inside the subject and the delivery of the subject to the student are the major concerns. By the principle, the SSE is the combination of knowledge, skill and values of the society. It is the composition of the academic disciplinary subjects of social sciences, such as, geography, history, sociology, anthropology, civics, economics, psychology, culture including numbers of social issues and agendas in an integrated form including the past events in the study enables and inspires students to understand the present and become the bona fide citizens. The present paper has focused the position of geography content in the social studies of school education curriculum in Nepal. It has been over viewed in the context of content incorporated inside the subject according to the grades from basic to the secondary level and the delivery systems in each chapter. At the end, the final outcomes have been summarized as a form of suggestions to improve the disciplinary development of geography content in the social studies of school education curriculum. The Third Pole: Journal of Geography Vol. 17: 1-20, 2017